March–May Snow Cover Extent Reconstruction for the Past Four Centuries Based on the Tree-Ring Early-Wood on the Southeastern Tibetan Plateau - Bing, Xiaojin; Yao, Qichao; Zhou, Feifei; Zheng, Zhuangpeng; Bai, Maowei; Jiang, Shixiong; Wang, Chongqing; Fang, Keyan (Frontiers in Ecology and Evolution, 2022)
The snow cover extent (SCE) on the southeastern Tibet Plateau (SETP) has an important impact on the dynamics of the East Asian winter monsoon and the runoff changes of the first and third largest rivers in Asia, namely, the Yangtze River and the Yarlung Zangbo River. Unfortunately, the shortness of instrumental SCE data of a few decades limits our ability to understand its long-term variability before the industrial era. Here, we developed Abies faxoniana tree-ring total ring width (TRW), early-wood width (EWW), and late-wood width (LWW) chronologies for the past four centuries at Little Qamdo Village (XQDV), Markam County, on the SETP. The most significant positive correlation (r = 0.62, p < 0.01) was found between the EWW chronology and SCE from March to May (SCE3–5). The SCE would affect the onset of the growing season through soil moisture, restricting the early-wood growth of trees. Thus, we presented a reconstruction of SCE3–5via EWW chronology since AD 1660 for SETP. We observed two abrupt changes from low to high around the years 1685 and 1998 for our reconstructed SCE3–5. In addition, we found that the positive anomalies of the reconstructed SCE3–5 after 1988 cohered with the distinct increase of the East Asian winter monsoon.